Cost-effectiveness of rilertinib versus osimertinib in second-line treatment in EGFR T790M resistance mutation advanced non-small cell lung cancer in China - Li, Xiangcheng; Lu, Yun; Lu, Yuqiong; Zhou, Mengyuan; Xie, Xiaoxi; Zhou, Yang; Qiu, Jiaxin; Dai, Zhanjing; Chang, Feng (Frontiers in Pharmacology, 2025)
BackgroundRilertinib, a third-generation epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI), has demonstrated a favorable efficacy and safety profile in adult patients with EGFR T790M + advanced NSCLC. This study examined the cost-effectiveness of rilertinib compared with osimertinib in the second-line treatment for EGFR T790M mutation-positive advanced NSCLC in the Chinese healthcare setting.MethodsA Markov model was developed to project economic and health outcomes. An unanchored matching-adjusted indirect comparison (MAIC) was used to compare the efficacy of rilertinib with osimertinib. Cost and utility values were obtained from Chinese health system data, public databases, and the published literature. Model robustness was assessed through deterministic and probabilistic sensitivity analyses (PSA).ResultsThe incremental life-years (LYs) and quality-adjusted life years (QALYs) for the rilertinib group versus the osimertinib group were 0.34 and 0.30, respectively. The total cost for the rilertinib group was $3,774.60 higher than that for the osimertinib group. The incremental cost-effectiveness ratio (ICER) for rilertinib group compared with osimertinib group was $12,786.08, which is lower than one time the GDP per capita ($13,444.68). Based on the willingness-to-pay (WTP) thresholds in China, rilertinib represented a cost-effective option. Relative efficacy and drug costs parameters were the key drivers of the model outcomes. PSA showed rilertinib’s cost-effective probabilities were 51.6% at one-time GDP per capita and 90.2% at three-times GDP per capita ($40,334.05) WTP threshold.ConclusionFrom a Chinese healthcare system perspective, second-line treatment of EGFR T790M resistance mutation advanced NSCLC with rilertinib may have cost-effectiveness compared with osimertinib.